Crash analysis of a conceptual electric vehicle with a damage tolerant battery pack. (December 2016) - Kukreja, J.; Nguyen, T.; Siegmund, T.; Chen, W.; Tsutsui, W.; Balakrishnan, K.; Liao, H.; Parab, N.
Abstract: In current electric vehicles, batteries fulfill only the role of power source and are stored within the passenger cabin, protected from external impact loads. This study considers a multifunctional, damage tolerant battery system which combines the energetic material with mechanically sacrificing elements that control mechanical stresses and dissipate energy. With such a multifunctional battery system in place it is proposed to place the battery pack into the secondary safe zone of a unibody-type vehicle. Full-vehicle crash analyses via finite element simulations are conducted for several battery pack configurations, thereby comparing the multifunctional battery system to battery packs with batteries alone and battery packs where cellular solids are used as energy absorbers. The analysis demonstrates the use of a multifunctional (damage tolerant and energy storage capable) battery system to ensure battery safety and aid in the energy absorption in a crash overall. The use of the multifunctional battery systems can aid in solving technology limitations of electric vehicles.